Abordagem do ensino de desvio padrão em livros didáticos - Francisco, Sérgio Luiz (Universidade Federal de São Carlos, 2013)
Teaching Statistics as part of the axis Treatment Information is seen by PCN (Parâmetros Curriculares Nacionais) as a tool for the interpretation of the world that surrounds the pupil, in view of the diversity of areas using the typical elements of Statistics (such as tables, graphs, etc.) in the dissemination of information. Hence, the need for teaching this subject should strive for contextualization of its contents and provide information for decision-making. The objective of this work was to present a didactic sequence that judges be more appropriate as the significance for the student with regard to the teaching of some of these elements of statistics, specifically the Standard Deviation, the application of an exercise in a class of 3rd. year of high school public school education in the city of Jahu. Together, adds that, after analysis of seven textbooks indicated by PNLEM programs (Programa Nacional do Livro Didático do Ensino Médio) and PNLD ((Programa Nacional do Livro Didático) as to approach the teaching of statistics, it was found that in one there is the option for this instructional sequence in which the settings of the approach is associated with the Normal Curve probabilities related to a frequency distribution. Expected to lead teachers and mentors to reflect on the teaching of this subject, both in performance in the classroom or guidance for professionals in education, as in the choice of books or other educational materials.
Keywords: Estatística; Desvios-padrão; Livros didáticos; Matemática; Statistics; Standard deviation; Textbooks; Math; CIENCIAS EXATAS E DA TERRA::MATEMATICA